Foundation of the cliometrics analysis of regional characteristics of the evolution of economic systems - Vladmir Leonidovich Beresnyov; Aleksey Petrovich Gorst (Экономика региона, 2013)
In the article, the methodical foundations of formation of simulating model of regional social and economic systems evolution reflecting admissible implementation variations of modern economic reform are considered, on conditions that some policy decisions were not made or was different. This approach allows not only to combine factual description with the studying of time series indicators characterizing a course of modern economic reform realization, but also to give a ranking score of received and possible results of the reformation. The authors of the article did not aim at giving answers to all questions while studying such a difficult issue as a modern economic reform, and, especially, at developing a full-scale model of reformation of the 1990th. For a start, it is necessary to prove that alternative options of implementation of the reform are possible, and there are some bifurcation points where attractor could change the direction. In the following, the research results can be a starting basis for collecting the statistical information necessary for calculations for a model of modern economic reform